Frameworks for discursive actions and practices of the law - Tessuto, Girolamo; Bhatia, V. K. (Vijay Kumar), 1942-; Engberg, Jan, 1962- (Legal discourse and communication., 2018)
"This volume provides descriptive and interpretive insights into the 'living' usage of language and other semiotice modes in building and performing the law across academic, professional and institutional contexts"--Back cover